2017
DOI: 10.1175/jcli-d-17-0156.1
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous Linkages between Clouds and Large-Scale Meteorology over the Southern Ocean in Observations and a Climate Model

Abstract: Instantaneous, coincident, footprint-level satellite observations of cloud properties and radiation taken during austral summer over the Southern Ocean are used to study relationships between clouds and large-scale meteorology. Cloud properties are very sensitive to the strength of vertical motion in the midtroposphere, and low-cloud properties are sensitive to estimated inversion strength, low-level temperature advection, and sea surface temperature. These relationships are quantified. An index for the meteor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 75 publications
6
36
0
Order By: Relevance
“…Over the Southern Ocean, locations with ascending motion in the CTL run are associated with a deep cloud layer with two relative maxima in cloud fraction near 400 hPa and 850 hPa (Figure a), consistent with observed vertical profiles of clouds in ascending regions of SH extratropical cyclones (Govekar et al, ; Wall et al, ). In contrast, locations with descending motion in the CTL run are associated with a shallow cloud layer below 700–850 hPa and little cloud fraction above, consistent with the observed prevalence of low cloud decks over subsiding regions of the Southern Ocean (Haynes et al, ).…”
Section: Resultssupporting
confidence: 84%
“…Over the Southern Ocean, locations with ascending motion in the CTL run are associated with a deep cloud layer with two relative maxima in cloud fraction near 400 hPa and 850 hPa (Figure a), consistent with observed vertical profiles of clouds in ascending regions of SH extratropical cyclones (Govekar et al, ; Wall et al, ). In contrast, locations with descending motion in the CTL run are associated with a shallow cloud layer below 700–850 hPa and little cloud fraction above, consistent with the observed prevalence of low cloud decks over subsiding regions of the Southern Ocean (Haynes et al, ).…”
Section: Resultssupporting
confidence: 84%
“…Bodas-Salcedo et al (2012) show that cloud regimes occupy distinct regions in the warm and cold sectors of the cyclone composite. Naud et al (2006) show that vertical pressure velocity at 500 hPa ( 500 ) provides a very good discrimination between the warm ( 500 < 0) and cold sectors ( 500 > 0) of the cyclone composite, also corroborated by a recent study (Wall et al, 2017). We therefore use 500 as a compositing variable to gain insight in the relationships between clouds and radiation in the midlatitudes.…”
Section: Methodssupporting
confidence: 66%
“… Note . The corresponding results of Wall et al () are shown for comparison. SST = sea surface temperature, EIS = estimated inversion strength.…”
Section: Discussionmentioning
confidence: 90%